Medical Family Businesses in Poland - Model and Managerial Challenges = Medyczne firmy rodzinne w Polsce - model i wyzwania kierownicze - Sułkowski, Łukasz; Woźniak, Andrzej; Sułkowska, Joanna (Zielona Góra: Faculty of Economics and Management Press)
There is a deficit of data in Poland about characteristics of family enterprises providing medical services. The medical sector in Poland faces a rapid development of family businesses and is diverse because it encompasses various size business entities that specialize in many possible aspects of the medical business.
Keywords: medyczne firmy rodzinne; sektor usług medycznych; sektor zdrowia w Polsce; wyzwania menedżerskie; model rodzinnych usług medycznych; medical family businesses; sector of medical services; health sector in Poland; managerial challenges; model of family medical services